1999
DOI: 10.1021/ic981409g
|View full text |Cite
|
Sign up to set email alerts
|

Retro Models of Pt Anticancer Drug DNA Adducts:  Chirality-Controlling Chelate Ligand Restriction of Guanine Dynamic Motion in (2,2‘-Bipiperidine)PtG2 Complexes (G = Guanine Derivative)

Abstract: Features of cisplatin-type anticancer drug adducts with nucleic acids and their constituents are clouded because they exist as a fluxional mixture of conformers. Retro-model adducts containing the specially designed chiral diamine ligand, Bip = 2,2'-bipiperidine, are dramatically less fluxional. Conformers of BipPtG(2) adducts with R,S,S,R and S,R,R,S asymmetric centers at the N, C, C, and N Bip chelate ring atoms and G = 5'-GMP, 5'-dGMP, 3'-GMP, or 9-ethylguanine are amenable to separate characterization. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
249
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(264 citation statements)
references
References 65 publications
15
249
0
Order By: Relevance
“…1). The cisplatin-purine adducts exist as a fluxional mixture of conformers, as free rotation around the Pt-N 7 bond allows an equilibrium between the HH and HT atropisomers, 69 leading to a high degree of conformational freedom. This is responsible for the broadened features observed in the corresponding optical vibrational spectra, as well as for the complexity of the measured INS pattern.…”
Section: View Article Onlinementioning
confidence: 99%
“…1). The cisplatin-purine adducts exist as a fluxional mixture of conformers, as free rotation around the Pt-N 7 bond allows an equilibrium between the HH and HT atropisomers, 69 leading to a high degree of conformational freedom. This is responsible for the broadened features observed in the corresponding optical vibrational spectra, as well as for the complexity of the measured INS pattern.…”
Section: View Article Onlinementioning
confidence: 99%
“…Structural models with both 5'-GMP nucleo-A C H T U N G T R E N N U N G tides in the anti conformation suggested that the 5'-phosphates are directed toward the cis amines in the DHT conformer and toward the cis nucleotide in the LHT conformer. Therefore, phosphate interactions with the cis amine (hydrogen-bond interaction) and with the platinum core (electrostatic interactions) will favor the DHT conformer, whereas phosphate interactions with the cis guanine (hydrogen-bond interaction with cis-5'-GMP N1H) [55][56][57][58] will favor the LHT conformer. However, even for those cases in which our choice of carrier ligand restricted the rotation about the PtÀN7 bond, these adducts are rendered very dynamic by rapid motions involving rotation about the N9 À C1' and the C4' À C5' bonds, and interchange among a very broad range of sugar puckers.…”
Section: Introductionmentioning
confidence: 99%
“…We employed neutral pH because the phosphate group is fully deprotonated, favoring hydrogen bonding and the LHT conformer. [55][56][57][58] With this strategy we were able to obtain, for the first time, crystals of a pure LHT rotamer, [bis(guanosine-5'-monophosphate(-2))-…”
Section: Introductionmentioning
confidence: 99%
“…Complexes (9d) and (17) have been used to investigate the dynamic behaviour of guanine residues and derivatives after platinum binding [22,70,71]. In the first place, these compounds have been tested only with guanines or their derivatives and not with nucleotides, providing only few information about their real effect on DNA conformation.…”
Section: Identified Factors Affecting Cytotoxic Activity Of Anticancementioning
confidence: 99%